MuiCSer: A Process Framework for Multi-disciplinary User-Centred Software Engineering Processes - Haesen, Mieke; Coninx, Karin; Van den Bergh, Jan; Luyten, Kris (Engineering Interactive Systems, 2008)
In this paper we introduce MuiCSer, a conceptual process framework for Multi-disciplinary User-centred Software Engineering (UCSE) processes. UCSE processes strive for the combination of basic principles and practices from software engineering and user-centred design approaches in order to increase the overall user experience with the resulting product. The MuiCSer framework aims to provide a common understanding of important components and associated activities of UCSE processes. As such, the conceptual framework acts as a frame of reference for future research regarding various aspects and concepts related to this kind of processes, including models, development artefacts and tools. We present the MuiCSer process framework and illustrate its instantiation in customized processes for the (re)design of a system. The conceptual framework has been helpful to investigate the role of members of a multi-disciplinary team when realizing artefacts in a model-based approach. In particular process coverage of existing artefact transformation tools has been studied.